Rachunek kosztów w przedsiębiorstwach mleczarskich jako czynnik wzrostu konkurencyjności - Szczubełek, Grzegorz; Romaniuk, Krystyna (Cost Account at Dairy Plants as An Element of Increasing Competitive Capacity, 2005)
In order to successfully compete on the EU market, Polish dairy plants can apply numerous strategies, including a cost strategy. The effectiveness of pursuing this strategy, aimed at achieving competitive edge, is directly related to the reliability of information provided by the cost account system at a given enterprise.Results of this study show that cost accounts applied at dairy plants provide unreliable information on the production costs of particular assortments of goods. This concerns especially settlements of raw material costs and their allocation to individual cost categories.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 321-325